Beneficiary Assessment: An Approach Described - Salmen, Lawrence (World Bank, 2002)
Beneficiary assessment is a tool for managers who wish to improve the quality of development operations. This is an approach to information gathering which assesses the value of an activity as it is perceived b y its principal users. The approach is qualitative in that it attempts to derive understanding from shared experience as well as observation , and gives primacy to the centrality of the other person’s point of v iew. As the Bank and others engaged in development activities seek to do their work better, one key indicator will need to be how the ultima te customer, or intended beneficiary, assesses the value of this work, project or policy, as it affects his or her life. The illumination of how an intended beneficiary appreciates a planned or ongoing developm ental activity is the primary objective of this approach. Beneficiary assessment is a systematic inquiry into people’s values and behavior i n relation to a planned or ongoing intervention for social and economi c change. This method draws heavily from the tradition in social scien ce known as "qualitative research...that fundamentally depends on watc hing people in their own territory and interacting with them in their own language, on their own terms" (Kirk and Miller). Yet beneficiary a ssessment also includes direct observation, incorporating simple count ing, and is expressed in quantitative terms. The ultimate goal of bene ficiary assessment is to reveal the meaning people give to particular aspects of their lives so that development activities may better enhan ce people’s ability to improve their own living conditions, as they se e fit. This demands close rapport between the practitioner of this app roach, the beneficiary and the development manager. The beneficiary as sessment approach is not intended to supplant the questionnaire survey but to provide reliable qualitative, indepth information on the socio -cultural conditions of a beneficiary population which is intended to be of immediate use to managers and policymakers responsible for impro ving people’s lives.